Gaze-shift dynamics in subjects with and without symptoms of convergence insufficiency: influence of monocular preference and the effect of training - van Leeuwen, Anna F; Westen, Marion J; van der Steen, Johannes; de Faber, Jan-Tjeerd H.N; Collewijn, Han (Vision research (Oxford), 1999)
We studied gaze-shift dynamics during several gaze-shift tasks and during reading, in five subjects with convergence insufficiency (C.I., a diminished ability to converge), and in ten subjects without C.I. Furthermore, we studied the effect of vergence training in order to verify previous claims that orthoptic exercises can improve vergence performance. We recorded binocular eye movements with the scleral coil technique. Subjects switched fixation between nearby and distant light emitting diodes (LEDs) arranged in isovergence arrays (distances 35 and 130 cm) in a dimly lit room. In both the C.I. and non-C.I. group, two classes of subjects occurred: vergence responders and saccadic responders. During pure vergence tasks, saccadic responders made saccades with no or little vergence; vergence responders made vergence movements with no or small saccadic components. In saccadic responders, fixation of nearby targets was monocular. Subjects with a preferred eye, according to our determination, used the preferred eye. The five C.I. subjects showed idiosyncratic responses with insufficient vergence during most trials. They all had a tendency to alternate fixation between the left and right eye. Vergence–version tasks always elicited larger vergence components than pure vergence tasks. During a reading task, vergence angles were more accurate than during gaze-shifts between LEDs. After the pre-training sessions, nine subjects (one of which had C.I.) practised a pure vergence task three times a day for at least 2 weeks. Vergence amplitudes of four of these subjects were larger after training. We conclude that vergence training can change oculomotor performance. Although C.I. is often associated with abnormal vergence dynamics, there are no typical C.I. vergence dynamics. Unstable monocular preferences may play a role in the aetiology of C.I.